Decentralized model of financial and investment provision of nature protection and nature exploitation activities: specific formation in urban and rural territorial communities - Medynska, N.; Kolosa, L.; Hunko, L.; Humenyak, R.; Lakhmatova, O. (Land Management, Cadastre and Land Monitoring, 2023)
It has been established that increasing the efficiency of solving the problems of improving the environment and the rational involvement of natural resources in the reproductive process depends on the formation of a decentralized model of financial and investment support for nature protection and nature exploitation activities, which will make it possible to strengthen the investment focus of natural resource and environmental payments, which are concentrated in local budgets. It is substantiated that the key element of the decentralized model of financial and investment support for nature protection and nature exploitation activities is the increase in the share of the transfer of environmental tax and rent and fees for the use of other natural resources to local government budgets with their further accumulation in special environmental funds. It has been proven that it is worth applying a differentiated approach to the formation of a decentralized model of financial and investment support for nature protection and nature exploitation activities for urban and rural territorial communities, based on the significant gap between the size of the public financial potential in these categories of communities. It has been established that the formation of Environmental Protection Funds, where 100% of environmental tax, 30% of rent and fees for the use of other natural resources will be concentrated, should be the main link of the decentralized model of financial and investment support for nature protection and nature exploitation activities in urban territorial communities. 10% of the net profit of utilities. Making informed decisions about land use in both urban and rural territorial communities requires appropriate information support. It is substantiated that additional sources of filling the Environmental Protection Funds of urban territorial communities should be considered the receipt of funds accumulated in connection with the emission of green bonds of a local loan, the implementation of public-private partnership agreements, the participation of local governments in the implementation of grant programs, the receipt of financial assistance from international environmental protection organizations and governments of foreign countries. It was established that in rural territorial communities, the dominant role in financial and investment provision of solving environmental problems should remain at the oblast level of local self-government and regional executive power.Key words: financial and investment support, decentralized model, ecological tax, nature conservation territories, territorial community, budget, ecological investments.
Keywords: financial and investment support; decentralized model; ecological tax; nature conservation territories; territorial community; budget; ecological investments